1991
DOI: 10.1159/000226884
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Medroxyprogesterone Acetate versus Oophorectomy as First-Line Therapy of Advanced Breast Cancer in Premenopausal Patients

Abstract: Forty premenopausal patients with advanced breast cancer entered a prospective and randomized study in which high-dose medroyxprogesterone acetate (HD MAP) and oophorectomy (OPX) were compared. All the patients were first treated for advanced disease. Twenty-two patients received HD MAP (1,000 mg b.i.d. p.o.) and 18 patients received OPX. Complete remission (CR) was achieved in 2 (9%) in the HD MAP group and in 2 (11 %) in the OPX group for a duration of 20–24 and 30–54 months respectively. Partial remission (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Thigpen et al (10) reported that serum level of medroxyprogesterone acetate became 600 and 1,900 nmol/L in endometrial cancer patients who have received oral medroxyprogesterone acetate in a dose of 200 mg/d (low dose; n = 145) and 1,000 mg/d (high dose; n = 154), respectively, and the overall clinical response rate was not significantly different in these groups (25% in the low-dose group and 15% in the high-dose group). Effects of medroxyprogesterone acetate were also reported in breast cancer patients when medroxyprogesterone acetate plasma levels were higher than f500 nmol/L (41), and the overall clinical responsive rate of patients who received high-dose medroxyprogesterone acetate was 54% (42). In addition, Nishimura et al (43) reported that the clinical responsive rate for oral medroxyprogesterone acetate was not significantly different between 400 mg/d (40%) and 800 mg/d (58%) in breast cancer patients treated with medroxyprogesterone acetate, but four of the six patients who did not respond to the 600 or 800 mg/d dose achieved a clinical response when given 1,200 mg/d of medroxyprogesterone acetate.…”
Section: Discussionmentioning
confidence: 97%
“…Thigpen et al (10) reported that serum level of medroxyprogesterone acetate became 600 and 1,900 nmol/L in endometrial cancer patients who have received oral medroxyprogesterone acetate in a dose of 200 mg/d (low dose; n = 145) and 1,000 mg/d (high dose; n = 154), respectively, and the overall clinical response rate was not significantly different in these groups (25% in the low-dose group and 15% in the high-dose group). Effects of medroxyprogesterone acetate were also reported in breast cancer patients when medroxyprogesterone acetate plasma levels were higher than f500 nmol/L (41), and the overall clinical responsive rate of patients who received high-dose medroxyprogesterone acetate was 54% (42). In addition, Nishimura et al (43) reported that the clinical responsive rate for oral medroxyprogesterone acetate was not significantly different between 400 mg/d (40%) and 800 mg/d (58%) in breast cancer patients treated with medroxyprogesterone acetate, but four of the six patients who did not respond to the 600 or 800 mg/d dose achieved a clinical response when given 1,200 mg/d of medroxyprogesterone acetate.…”
Section: Discussionmentioning
confidence: 97%
“…In the context of failure of prior endocrine therapy, median durations of response of up to 10 months have been reported (Brufman et al 1994, Birrell et al 1995b, Abrams et al 1999, Bines et al 2014. Progestins have similar efficacy to tamoxifen, oophorectomy and aminoglutethimide (an AI and inhibitor of cholesterol conversion to steroids) in comparative trials in the metastatic setting (Ingle et al 1982, Ettinger et al 1986, van Veelen et al 1986, Canney et al 1988, Muss et al 1988, Lundgren et al 1989, Martoni et al 1991). An adjuvant study in high-risk breast cancer demonstrated no difference in outcomes between tamoxifen for 1 year, tamoxifen for 2 years or tamoxifen for 6 months followed by megestrol acetate for 6 months (Andersen et al 2008).…”
Section: Pr-directed Strategies For Treating Breast Cancermentioning
confidence: 99%
“…The adjuvant effect of medical castration induced by LH-RH analogues, such as goserelin, may also be potentiated by the concomitant use of tamoxifen (Rutqvist, 1999); this association may even outshine the effect of CMF (Jakesz et al, 1999). At this point, it must be remembered that part of the HD-MPA hormonal activity could also be related to a general hypophyseal adrenal and gonadal blockage; so, part of its antitumoral activity could be related to this castrative effect (Van Veelen et al, 1985;Martoni et al, 1991;Paridaens et al, 1986).…”
Section: Cmfmentioning
confidence: 99%
“…In those trials, as already observed, the dose of progestogen (Mattson, 1980;Löber et al, 1981;Cavalli et al, 1984;Tchekmedyian et al, 1986;Van-Veelen et al, 1986) could be of paramount for determining the antitumor efficacy of these agents: high doses of drugs could significantly increase the response rate and even, in some observations, prolong time to treatment failure and survival (Mattson, 1980;Löber et al, 1981;Cavalli et al, 1984;Tchekmedyian et al, 1986;Van Veelen et al, 1986). Furthermore, like first-line hormonotherapy for advanced ER positive breast cancers, in premenopausal patients, HD-MPA developed antitumour activity at least equivalent, if not superior, to oophorectomy (Martoni et al, 1991). The addition of medroxyprogesterone acetate in high dosage (i.e.…”
mentioning
confidence: 99%